Why the UK Should Consider Gene Expression Testing in Prostate Cancer. Issue 3 (March 2020) - Dess, R.T.; Spratt, D.E.
Abstract: There is an increase in the use of prognostic gene expression biomarkers in the USA for the personalisation of treatment for men with localised and recurrent prostate cancer. However, these are not available in the UK. This overview will cover the need to shift from subjective histological phenotypes (e.g. Gleason grade) to more objective biological genotypes, review the suboptimal performance of clinical and pathological variables to accurately risk stratify patients and discuss the growing body of consistent work that has shown that genomic classifiers more accurately discriminate which men harbour indolent or biologically aggressive disease, independently of grade or stage. Overall, we will discuss the need for improved prognostic biomarkers and why the UK and the National Institute for Health and Care Excellence guidelines should move beyond the now 20-year-old three-tier D'Amico risk classification schema to guide the management of prostate cancer in the modern era.